Pengembangan Edugame pada Materi Sistem Saraf untuk Siswa SMA - Firdaus, Zahra; Zubaidah, Siti; Munzil, Munzil (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The complex material of the nervous system often makes high school students feel challenged due to limited teaching time and monotonous learning media. Designing an interactive and enjoyable edugame can simplify students' understanding of abstract concepts and increase their motivation to learn. This study aims to develop an educational game on the nervous system that is valid and practical as a recommended learning medium for high school students. The development uses the Multimedia-Based Instructional Design model by Lee & Owens, which consists of analysis, design, development and implementation, and evaluation. The sample in this study consists of 32 high school students majoring in Science. The data analysis of the validation results is done using a percentage formula, while the questionnaire reliability is analyzed using Cronbach's alpha. The results of media validation showed a score of 95%, material validation reached 100%, validation by practitioners obtained 95%, and the practicality test of the media achieved 96.7%. This educational game on the nervous system can be recommended as one of the learning media for the nervous system material.